2015
DOI: 10.1002/jrs.4696
|View full text |Cite
|
Sign up to set email alerts
|

Raman analysis of amorphous silicon ruthenium thin films embedded with nanocrystals

Abstract: We report the Raman analysis of both as‐deposited and annealed amorphous silicon ruthenium thin films embedded with nanocrystals. In the Raman spectra of as‐deposited films, variations of TO peak indicate a short‐range disorder of a‐Si network with an increase of Ru concentration. The substitutional Ru atoms lower the concentration of Si―Si bonds and suppress the intensity of TO peak, but have less effect on TA, LA and LO peaks. In the Raman spectra of annealed films, characteristic parameters confirm the upgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Ruthenium dyes have been successfully used to generate electrostatically stabilized gold colloides, whereas Ru/TiO 2 has been employed as a catalyst in the selective methanation of CO . A number of recent studies are devoted to the materials that incorporate ruthenium, for example, the ruthenium doped ZnO nanorods, amorphous silicon ruthenium thin films embedded with nanocrystals, Ru‐doped ZnS quantum dots, ruthenium complexes bound to CdSe nanoparticles, hybrid materials including the Zn (II)‐Ru (II) complexes, trinuclear ruthenium complex, Ru‐red, and isolated and agglomerated gold nanoparticles functionalized with a ruthenium dye …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruthenium dyes have been successfully used to generate electrostatically stabilized gold colloides, whereas Ru/TiO 2 has been employed as a catalyst in the selective methanation of CO . A number of recent studies are devoted to the materials that incorporate ruthenium, for example, the ruthenium doped ZnO nanorods, amorphous silicon ruthenium thin films embedded with nanocrystals, Ru‐doped ZnS quantum dots, ruthenium complexes bound to CdSe nanoparticles, hybrid materials including the Zn (II)‐Ru (II) complexes, trinuclear ruthenium complex, Ru‐red, and isolated and agglomerated gold nanoparticles functionalized with a ruthenium dye …”
Section: Introductionmentioning
confidence: 99%
“…[23] In addition to the DSSC and biomedicine, other fields of application emerge as well. Ruthenium dyes have been successfully used to generate electrostatically stabilized gold colloides, [24] whereas Ru/TiO 2 has been employed as a catalyst in the selective methanation of CO. [25] A number of recent studies are devoted to the materials that incorporate ruthenium, for example, the ruthenium doped ZnO nanorods, [26] amorphous silicon ruthenium thin films embedded with nanocrystals, [27] Ru-doped ZnS quantum dots, [28] ruthenium complexes bound to CdSe nanoparticles, [29] hybrid materials including the Zn (II)-Ru (II) complexes, [30] trinuclear ruthenium complex, Rured, [31] and isolated and agglomerated gold nanoparticles functionalized with a ruthenium dye. [24] The Raman scattering, a sensitive, nondestructive characterization tool, has been used to obtain information about sample quality as well as to analyze specific aspects of lattice dynamics, namely, the isotopic effects, phonon lifetimes, position of doping ions in a host lattice, and presence of impurities that are undetectable by the Xray analysis.…”
Section: Introductionmentioning
confidence: 99%
“…They found in the Raman spectra of as‐deposited films, variations of transverse optical (TO) peak indicate a short‐range disorder of a‐Si network with an increase of Ru concentratioin. The substitutional Ru atoms lower the concentration of Si‐Si bonds and suppress the intensity of TO peak, but have less effect on transvere acoustic (TA), longitudinal acoustic (LA) and longitudinal optic (LO) peaks . Nguyen and Joo studied surface anchoring mode‐dependent hydrolysis reactions of hydrazone groups on gold examined by pH‐dependent Raman spectroscopy.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The substitutional Ru atoms lower the concentration of Si-Si bonds and suppress the intensity of TO peak, but have less effect on transvere acoustic (TA), longitudinal acoustic (LA) and longitudinal optic (LO) peaks. [72] Nguyen and Joo studied surface anchoring mode-dependent hydrolysis reactions of hydrazone groups on gold examined by pH-dependent Raman spectroscopy. Their results revealed that the pH-dependent cleavage reactions may vary depending on the surface anchoring modes of the adsorbates.…”
Section: Carbon Nanotubes Carbon Materials Graphene and Filmsmentioning
confidence: 99%
“…Based on above considerations, we introduce Ru instead of Ge, into a-Si to adjust the bandgap of a-Si 1-x Ru x thin films. Since the structural and electrical properties of a-Si 1-x Ru x thin films have been reported in our early researches [15,16], in this work, efforts are focused on optical properties of the thin films. Random nano-holes are fabricated on the back surface of silicon substrates by chemical etching, and a layer of a-Si 1-x Ru x thin film is deposited on them subsequently.…”
Section: Introductionmentioning
confidence: 99%